The Influences of Exchange Rates, Money Supplies, and Interest Rates on IHSG Using Inflation as a Moderating Variable - Hakim Muttaqim; Jamaluddin; M. Saleh (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The Indonesia Composite Stock Price Index is highly responsive to macroeconomic conditions, making an understanding of these relationships essential for market participants in developing economies. This study examines the influence of exchange rates, money supply, and interest rates on the IHSG, with inflation analyzed as a moderating variable to assess its role in shaping these interactions. A quantitative method is employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) on monthly data from January 2017 to December 2024. The data were sourced from Bank Indonesia, the Central Bureau of Statistics, and the Indonesia Stock Exchange (IDX). Findings reveal that exchange rates negatively and significantly affect the Composite Stock Price Index, while money supply and interest rates have positive and significant impacts. Inflation contributes positively to stock index performance and serves as a moderating factor, although its effect is relatively smaller. The study highlights the importance of macroeconomic stability for capital market resilience. For investors, attention to inflation and interest rate trends can enhance portfolio strategies. For policymakers, coordinated monetary policy is vital to reduce market uncertainty and sustain investor trust in Indonesia’s stock market.